Manipulation of droplets using surface acoustic waves - Liew, Yeo Liang (2018)
In recent years, surface acoustic wave (SAW) that were generated by interlocking patterns of the interdigital transducers on a piezoelectric substrate has integrated into lab-on-a-chip (LOC) microfluidic devices. Manipulation of droplet in microfluidic devices has great potential in chemistry and biology. These devices can manipulate small quantities of volumes and reagents to carry out separations and detections with high resolution and sensitivity. Other advantages include low cost and shorter processing duration. In this report, we present the manipulation of droplet with the help of the theoretical study, investigation of the RF power and the applications of microfluidics such as mixing and manipulation in microchannel.